2019
DOI: 10.17305/bjbms.2019.4345
|View full text |Cite
|
Sign up to set email alerts
|

The effects of exercise on vascular markers and C-reactive protein among obese children and adolescents: An evidence-based review

Abstract: Numerous studies have evaluated the effects of exercise training on obese children and adolescents. However, the impact of aerobic and/or resistance exercise alone, without any other interventions, on vascular markers and C-reactive protein (CRP) in obese children and adolescents is still not clear. We performed a literature search in Ovid Medline, PubMed, and SCOPUS databases to identify articles on the effects of exercise on vascular markers and CRP among obese children and adolescents, published between Jan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…However, studies found that a combination of aerobic exercise and resistance exercise in treating obesity improved both cardiorespiratory fitness and life quality in patients with obesity-related cardiometabolic diseases. [71] Numerous clinical studies examined the effect of exercise therapy alone or combined lifestyle intervention therapies, including excise therapy, nutrition limitation, and surgical procedures. A total of 109 children with a mean age of 11 years were enrolled in a clinical study to assess 5 weeks of exercise training.…”
Section: Beneficial Effects Of Physical Activity On Pediatric Obesity...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies found that a combination of aerobic exercise and resistance exercise in treating obesity improved both cardiorespiratory fitness and life quality in patients with obesity-related cardiometabolic diseases. [71] Numerous clinical studies examined the effect of exercise therapy alone or combined lifestyle intervention therapies, including excise therapy, nutrition limitation, and surgical procedures. A total of 109 children with a mean age of 11 years were enrolled in a clinical study to assess 5 weeks of exercise training.…”
Section: Beneficial Effects Of Physical Activity On Pediatric Obesity...mentioning
confidence: 99%
“…Regular exercise could improve energy metabolism, strengthen the function of various organs, including the heart, blood vessels, lung, brain, bone, and muscle, improve cardiovascular disease risk profile, reduce cardiovascular events, and decrease hospitalization of patients with obesity-related diseases. [ 70 , 71 , 72 ] There are two significant types of exercise, aerobic exercise and resistance exercise. Aerobic exercise induces multiple beneficial effects, including improvement in maximal oxygen consumption (VO 2 max) and cardiorespiratory fitness without significantly affecting the muscle strength.…”
Section: Beneficial Effects Of Physical Activity On Pediatric Obesity...mentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis revealed that the effects of aerobic endurance exercise on IMT did not show any statistical significance in healthy adults 15 . The decrease of IMT was proved in obese children and adolescents 9 17 . In this meta-analysis, ET improved IMT in overweight or obese participants who were younger than 60 years, but the effect was insignificant in aged participants.…”
Section: Discussionmentioning
confidence: 91%
“…Regular moderate-high intensity physical activity is considered to be bene cial to control blood pressure. Studies showed that the planned physical activity lowered SBP and DBP in children [9,10], which may be related to the effect of aerobic exercise on improving vascular markers ( pulse wave velocity, PWV; carotid intima-media thickness, CIMT) [11]. Torrance et al [12] recommended 40 minutes of moderate to vigorous aerobic exercise 3-5 days per week to improve vascular function and lower blood pressure in obese children.…”
Section: Introductionmentioning
confidence: 99%